Sundanese ethnoastronomy-based astronomy bulletin as an alternative to astronomy learning: A feasibility test - Salsabila Husna; Tsania Nur Diyana (Jurnal Inovasi Teknologi Pendidikan, 2023)
This study aims to determine the feasibility of independently developing a Sundanese ethnoastronomy-based astronomy bulletin as an alternative astronomical learning media. This research uses the ADDIE method, which consists of five stages, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation (5)Â  Evaluation. However, this research only reached the determination of the feasibility of the bulletin, so the implementation and evaluation stages still needed to be carried out. The subjects of this study were one physics education lecturer and one physics teacher. The results of the feasibility test on the three indicators include (1) content validation tests obtained an average value of 81.25%, (2) language validation tests obtained an average value of 81.25%, and (3) presentation validation tests obtained a value of 80%, and the overall indicators showed reliable results. Therefore, the bulletin learning media developed is feasible and can be used as an alternative learning media for Sundanese ethnoastronomy-based astronomy.Â